2002
DOI: 10.1097/00024720-200202000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Does Anterior Plating Maintain Cervical Lordosis Versus Conventional Fusion Techniques? A Retrospective Analysis of Patients Receiving Single-Level Fusions

Abstract: A retrospective review of medical records and radiographs of patients receiving anterior cervical discectomy and fusion (ACDF) without anterior plating and with anterior plating was performed. The objective of the study was to determine whether a difference exists in cervical lordotic alignment between subjects undergoing single-level ACDF with and without anterior cervical plating instrumentation for symptomatic cervical disc disease. Collapse or settling of grafted bone into the vertebral endplates with resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…Normal lordotic alignment is one of the most important factors contributing to good motion and function of the cervical spine [29]. Postoperative kyphosis at a fused cervical motion segment has been reported frequently, especially in uninstrumented anterior fusion [28], with an incidence as high as 27.3% [13]. Sagittal malalignment after ACDF may relate to the cervical instability, postoperative axial pain, and the deterioration of neurological deficit, and may influence the functional recovery [7,12].…”
Section: Discussionmentioning
confidence: 99%
“…Normal lordotic alignment is one of the most important factors contributing to good motion and function of the cervical spine [29]. Postoperative kyphosis at a fused cervical motion segment has been reported frequently, especially in uninstrumented anterior fusion [28], with an incidence as high as 27.3% [13]. Sagittal malalignment after ACDF may relate to the cervical instability, postoperative axial pain, and the deterioration of neurological deficit, and may influence the functional recovery [7,12].…”
Section: Discussionmentioning
confidence: 99%
“…TMCs are sufficiently rigid and are designed to resist compression and torque [35]. The addition of an ACP resists bending forces and theoretically protects against dislodgement of the cage, helps in maintaining cervical lordosis [24,53], and is reported to have higher fusion rates [58,62].…”
Section: Groupmentioning
confidence: 99%
“…This study was graded Class II because of uncertainty regarding allocation concealment and the subjectivity of the VAS. 41 Troyanovich et al 34 reported on 47 patients who underwent ACDF or ACDFI, 21 and 26 patients, respectively. An independent observer assessed overall lordosis pre-and postoperatively.…”
Section: Resnick and Trostmentioning
confidence: 99%